The influence of high-strength bolt preload loss on structural mechanical properties. (15th November 2022) - Kong, Qingzhao; Li, Yang; Wang, Shuyin; Yuan, Cheng; Sang, Xiaohan
Highlights: The influence of high-strength bolt preload loss on structural mechanical properties is carried out by means of experiment, finite element and theoretical calculation. Increasing the bolt preload only has function on the slip connection strength of the structure, but slight on the ultimate bearing capacity. The result of numerical model is in good agreement with the experimental data. One theoretical model is established and verified by the experimental and numerical data. Abstract: High-strength friction bolts in engineering are affected by corrosion, fatigue and other factors in long-term use, and preload loss is a common phenomenon in engineering. In order to study the influence of the preload loss of high strength bolt group on the basic mechanical properties of structures, a flexural test of steel beams connected by high strength friction bolt group was numerically and experimentally investigated in this study. The variable between each specimen is the preload value of the high-strength bolt group. To this end, the strength of bolt connection, the rotational stiffness of the whole structure and the local joint, the deformation distribution of the structure, slippage curves, cross-section strain and ultimate bearing capacity are evaluated and discussed. In addition, the mechanics of the structure at different sliding stages are theoretically calculated. The research results show that the preload of the high-strength bolt group loss will reduce the connection strength and structure stiffness, but has very limited influence on the ultimate bearing capacity of the structure.